Genetic variation in toll‐like receptors and retinoic acid‐inducible gene I and outcome of hepatitis C virus infection: a candidate gene association study. Issue 8 (13th November 2013) - Clausen, L. N.; Ladelund, S.; Weis, N.; Bukh, J.; Benfield, T.
Summary We evaluated the effects of genetic variation in toll‐like receptors (TLR), retinoic acid‐inducible gene I (RIG‐I) and their signalling pathways on spontaneous hepatitis C virus (HCV) resolution. We screened 95 single‐nucleotide polymorphisms (SNPs) in 22 genes. SNPs significantly associated with resolution in the discovery cohort were genotyped in a validation cohort. Multivariate logistic regression adjusted for sex, hepatitis B surface antigen, HIV infection and the interleukin‐28B rs12979860 SNP was performed in the combined cohort. Haplotype reconstruction and linkage disequilibrium analysis were performed. srs2233437, rs730775 and rs28362857 in Inhibitor of NF‐kB ε (IkBε) and rs352140 in TLR9 were associated with spontaneous HCV resolution (P ≤ 0.05) in the discovery cohort (n = 308). In the validation cohort (n = 216), we replicated a significant association with HCV resolution for two SNPs in the IkBε, rs2233437 and rs730775. Presence of one or two of the variant allele in rs2233437 had more than twofold higher odds of resolution in adjusted logistic regression (adjusted odds ratio (aOR), 2.6; (95% CI, 1.4, 4.8) P = 0.002). We identified polymorphisms in the IkBε gene associated with spontaneous HCV resolution in two independent cohorts.